Novel Visceral-Anastomosis-First Approach in Open Repair of a Ruptured Type 2 Thoracoabdominal Aortic Aneurysm: Causes behind a Mortal Outcome - Einar Dregelid; Alireza Daryapeyma (Case Reports in Vascular Medicine)
Case reports to analyze causes and possible prevention of complications in a new setting are important. We present an open repair of a ruptured type 2 thoracoabdominal aortic aneurysm in a 78-year-old man. Lower-body perfusion through a temporary extracorporeal axillobifemoral arterial prosthesis shunt was combined with the use of a branch to the permanent aortic prosthesis to enable rapid visceral revascularization using a visceral-anastomosis-first approach. The patient died due to transfusion-induced capillary leak syndrome and left colon necrosis; the latter was probably caused by a combination of back-bleeding from lumbar arteries causing a steal effect, an accidental shunt obstruction, and hemodynamic instability towards the end of the operation. The visceral-anastomosis-first approach did not contribute to the complications. This approach reduces the time when visceral organs are perfused only via collateral arteries to the time needed for suturing the visceral anastomoses. This may be important when collateral perfusion is marginal.